Cosmetic amputation of the fourth ray as possible outcome of thetraumatic amputation of the ring finger injury: a case report - Pedrazzini, A.; Calderazzi, F.; Bertoni, N.; Ceccarelli, F. (Acta Biomedica Atenei Parmensis, 2008)
The aim of this work is to describe a case of traumatic amputation of the fourth finger of the left hand. In its first phase, a treatment which consisted in a disarticulation at the level of the metacarpo-phalangeal joint was carried out; in the second phase, three months after this emergency treatment, a cosmetic amputation of the fourth metacarpal ray was required. Surgery was performed in accordance with the technique described by Bunnell, which consisted in the disarticulation of the fourth metacarpal, together with radial traslation of the fifth ray. Eighteen months after the operation The patient reported the absence of any subjective problems, with complete functional recovery of the hand that had been operated on. By that time she was back at her job; she also was satisfied with the cosmetic results that had been achieved.